Biopolymer-based membranes associated with osteogenic growth peptide for guided bone regeneration - Saska, Sybele [UNESP]; Pigossi, Suzane C [UNESP]; Oliveira, Guilherme J. P. L. [UNESP]; Teixeira, Lucas N.; Capela, Marisa V. [UNESP]; Gonçalves, Andreia [UNESP]; De Oliveira, Paulo T.; Messaddeq, Younès [UNESP]; Ribeiro, Sidney J. L. [UNESP]; Gaspar, Ana Maria Minarelli [UNESP]; Marchetto, Reinaldo [UNESP] (IOP Publishing, 2018)
Barrier membranes for guided bone regeneration (GBR) mainly promote mechanical maintenance of bone defect space and induce osteopromotion. Additionally, biopolymer-based membranes may provide greater bioactivity and biocompatibility due to their similarity to extracellular matrix (ECM). In this study, biopolymers-based membranes from bacterial cellulose (BC) and collagen (COL) associated with osteogenic growth peptide (OGP(10-14)) were evaluated to determine in vitro osteoinductive potential in early osteogenesis; moreover, histological study was performed to evaluate the BC-COL OGP(10-14) membranes on bone healing after GBR in noncritical defects in rat femur. The results showed that the BC-COL and BC-COL OGP(10-14) membranes promoted cell proliferation and alkaline phosphatase activity in osteoblastic cell cultures. However, ECM mineralization was similar between cultures grown on BC OGP(10-14) and BC-COL OGP(10-14) membranes. In vivo results showed that all the membranes tested, including the peptide-free BC membrane, promoted better bone regeneration than control group. Furthermore, the BC-COL OGP(10-14) membranes induced higher radiographic density in the repaired bone than the other groups at 1, 4 and 16 weeks. Histomorphometric analyses revealed that the BC-COL OGP(10-14) induced higher percentage of bone tissue in the repaired area at 2 and 4 weeks than others membranes. In general, these biopolymer-based membranes might be potential candidates for bone regeneration applications.
Keywords: bacterial cellulose; barrier membrane; collagen